Effects of mentoring relationship heterogeneity on student outcomes in summer undergraduate research. Issue 3 (4th March 2021) - Morales, Danielle X.; Grineski, Sara E.; Collins, Timothy W.
ABSTRACT: Faculty-mentored summer undergraduate research experiences (SUREs) have been shown to increase the diversity of students pursuing research careers. No existing studies have approached the issue of broadening participation in STEM research training by focusing on mentoring relationship heterogeneity (MRH) in the context of SUREs. Increasing MRH occurs when a mentee does not match a mentor in terms of gender and race/ethnicity and when the mentee's research experience depends on relationships with multiple mentors. Drawing on data from a multi-sited SURE program, we examine the effects of MRH on student satisfaction and science identity. Results indicate that students' satisfaction was not significantly affected by MRH. Greater MRH predicted reduced science identity development, but high quality faculty-undergraduate mentoring interactions moderated this negative impact. MRH has the potential to become a positive influence on student training. Results suggest that mentors should strive to improve mentoring competencies in order to better support diverse students.